The new neighbors : a novel - Douglas, Claire (Journalist) (Harper, an imprint of HarperCollins Publishers, 2025)
When Lena overhears a conversation between her next-door-neighbors she thinks she must have misheard. The Morgans are a kind, retired couple who recently moved to their sleepy suburban street in Bristol where nothing ever happens. But to Lena it sounded very much like they were planning a crime. Her family and friends tell her she must be mistaken. Yet Lena can't stop thinking about that strange conversation. What if they really are about to do something terrible? What if she can prevent it?